MENDETEKSI EARNINGS MANAGEMENT DAN AKUN-AKUN YANG BERPENGARUH (Studi Pada Perusahaan Yang Melakukan Aktivitas Penawaran Saham Perdana Di Bursa Efek Jakarta) - OTTO - BUDIHARDJO; ALI - DJAMHURI; HARRY - SUSANTO (Wacana Journal of Social and Humanity Studies, 2009)
ABSTRACT Earnings Management (EM) is an effort performed by company management as financial report issuer on purpose to influence the readers and stakeholders behavior who rely on financial reports as their primary information source, in accordance with firm managements’ direction.   EM motivations may vary, from remuneration reason, merger and acquisition event, to comply with particular requirement and regulation, to initial public offering (IPO) motivation. This study revealed EM effort in IPO event due to management motivation to demonstrate good performance to public before and during such activity. This study took 50 IPO firms listed at Jakarta Stock Exchange (JSX) within 1998-2002. EM detection adopted Modified Jones Model as a powerful model to detect EM. Test result proved that EM was occurred on JSX IPO firms as stated by positive discretionary accruals (DA).                  Further study tried to reveal accounts used as EM tools. This study utilized linear regression with DA as fixed variable to indicate EM and predicted accounts on financial reports used as way to do EM as explanatory variables. Such explanatory variables are account receivable, account payable, inventory, accrued liability, accumulated depreciation, expenses (selling and general administrative) and other income (expense). Test result showed that only two variables statistically significant to dependent variable, i.e. DA, they were account receivable and account payable. This result supports a study by Marquardt and Wiedman (2002) who found that EM during IPO activity was influenced by account receivable in positive direction. However, this study does not support Wiedyaningdyah (2001) who concluded IPO activity in JSX during 1994-1997 was significantly influenced by liability (leverage). This study recommends investors or any other parties who rely on firm financial report during IPO activity on JSX to behave more conservative on net income as reported by related firms and considers account receivable and account payable as accounts need to be reviewed prior to any economical decision making related to the financial reports. Key words: Earnings Management, Discretionary Accruals, Initial Public Offerings (IPO).